Different performances in static and dynamic imagery and real locomotion. An exploratory trial - Fusco, Augusto; Iosa, Marco; Gallotta, Maria Chiara; Paolucci, Stefano; Baldari, Carlo; Guidetti, Laura (Frontiers in Human Neuroscience, 2014)
Motor imagery is a mental representation of an action without its physical execution. Recently, the simultaneous movement of the body has been added to the mental simulation. This refers to dynamic motor imagery (dMI). This study was aimed at analyzing the temporal features for static and dMI in different locomotor conditions (natural walking, NW, light running, LR, lateral walking, LW, backward walking, BW), and whether these performances were more related to all the given conditions or present only in walking. We have been also evaluated the steps performed in the dMI in comparison with the ones performed by real locomotion. Twenty healthy participants (29.3 ± 5.1 y. old) were asked to move towards a visualized target located at 10mt. In dMI, no significant temporal differences respect the actual locomotion were found for all the given tasks (NW: p=0.058, LR: p=0.636, BW: p=0.096; LW: p=0,487). Significant temporal differences between static imagery and actual movements were found for LR (p<0.001) and LW (p<0.001), due to an underestimation of time needed to achieve the target in imagined locomotion. Significant differences in terms of number of steps among tasks were found for LW (p<0.001) and BW (p=0.036), whereas neither in NW (p=0.124) nor LR (p=0.391) between dMI and real locomotion. Our results confirmed that motor imagery is a task-dependent process, with walking being temporally closer than other locomotor conditions. Moreover, the time records of dynamic motor imagery are nearer to the ones of actual locomotion respect than the ones of static motor imagery. Keywords: Walking, dynamic motor imagery, human locomotion, chronometry.